Thinking Level in Education: A Complete Revision of Anderson’s Taxonomy - Ichsan, Ilmi Zajuli; Rahmayanti, Henita; Purwanto, Agung; Vivanti Sigit, Diana; Kurniawan, Edi; Tanjung, Ardyanto; Putri Panjaitan, Ruqiah Ganda; Pertiwi, Nurlita; Swaran Singh, Charanjit Kaur (Pedagogika, 2023)
The study aimed to revise Anderson’s taxonomy and implement the new taxonomy in learning. The study used the descriptive method and there were 6 types of instruments used according to new taxonomy. The results showed that students’ knowledge scores were still in a very low category at the Natural science, Environment, and Social Science at School and University levels. This study concluded that a new taxonomy had been developed and its implementation indicated that students’ knowledge score was still very low.